Dynamic Analysis of Digital Twin System Based on Five-Dimensional Model. Issue 7 (April 2020) - Sun, Lei; Pei, Aigen; Qi, Xuan; Cao, Sheng; Yang, Ruibo; Liu, Xiaoke
Abstract: The practical application level of digital twinning technology has always been far from people's expectations. In order to make the digital twinning technology develop better, it is urgent to explore the internal causes of this kind of drop. Based on the theory of digital twinning five-dimensional model, combined with the actual situation of software development, dynamically analyze the working state of digital twin system, observe and discover the working conditions of various structural elements in the work of digital twin system, and propose the data of twins in digital twin system. The existence method, clear the concept of multiple virtual entities in the digital twin system, propose the principle that the service elements must be combined with the physical/virtual entities, summarize the organizational structure and operation rules of the digital twin system, and summarize the principles of a series of digital twin systems. The concept points out how to reduce manual operations to improve the operation of digital twin systems. The conclusions based on the five-dimensional model of the digital twin system are universal and can provide reference for the establishment and management of various types of digital twin systems.